Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 45



Work Step by Step

$(\frac{f}{g})(x)=\frac{f(x)}{g(x)}$ $=\frac{x^{2}+4x}{2-x}$ Plugin $x=-1$ into $\frac{x^{2}+4x}{2-x}.$ $(\frac{f}{g})(-1)=\frac{(-1)^{2}+4\times(-1)}{2-(-1)}=\frac{1-4}{2+1}=\frac{-3}{3}=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.